Nominalization and Its Role in the Formation of Noun Phrase in Japanese - Faquire, Razaul Karim (Universitas Muhammadiyah Yogyakarta, 2021)
This study sheds light on the yields of nominalization and their role in the formation of Noun Phrases in Japanese in an envisaged framework which considers nominalization to be a morphosyntactic process. Nominalization operates on the linguistic constituent to transform it into a derivative/transformed constituent. It brings forth derivative nouns by operating on the words other than nouns involving the process of derivation as well as action nominal constituent and nominal clause respectively involving the simultaneous process of desententialization and transformation, and the process of reduction of clausal properties from a finite clause. It fundamentally differs from the prevalent nominalizer approach, which derives bound-noun-headed nominals by juxtaposition of a dependent constituent with the nominalizers, e.g. no and koto. The derivative noun, bound-noun-headed constituent, action nominal constituent as well as nominal clause together form a grammatical category called nominals, which partake both as the head or the adnominal in the formation of NP involving certain grammatical rules. Â